Transformation of scientific knowledge into an information and cognitive scientific product of the digital age society - M. A. Zakharov; A. V. Shishkova (Вестник университета)
The processes associated with changes in approaches to the definition and research of the scientific knowledge concept in the digital society have been analyzed. The authors proceed from understanding of the nature of science through the scientific knowledge analysis as a scientific cognition result, thus arriving at the need to demarcate the concepts of scientific knowledge, scientific information, scientific data, and other cognitive constructs. The first part of the study examines these concepts through the prism of the information approach, constructivism, systemic approach, phenomenology, and postmodernism. The second part of the study addresses the question of whether knowledge can exist outside individual consciousness, have its own independent life in society, and be digitized. Two approaches have been considered. Within the framework of the first one, knowledge is a suprapersonal phenomenon and has the ability to exist independently outside its creator. Within the framework of the second one, when knowledge is detached from its creator, it loses its original form and is transformed into information capable of being commodified, which is not a complete reflection of knowledge. It has been shown that within the framework of the second approach digitalization leads to cognitive impoverishment of society due to the loss of the part of scientifi knowledge that cannot be digitized. As an alternative approach, the information and cognitive scientifi product of society concept, which can be used as a framework concept, has been proposed. This product is a set of explicit scientific knowledge and socially significant scientific information that actively circulates in the information space of society.